Визначення впливу способу збирання з’єднань з натягом “твердосплавна вставка–матриця” на їх несучу здатність - Корнута, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The results of simulation are compared for pressure coupling constructions which are assembled
in different ways. Reasons of advantage of the thermal assembling above assembling by
“press in” are found out. Advantages of new construction are set.